Evangeliefortællingens udsigelse - Davidsen, Ole (Religionsvidenskabeligt tidsskrift, 1990)
Inspired by the work of A. J. Greimas and Claude Bremond the article presents an elementary definition of the enunciation of the narrative, its narration:1) The narrator (enunciator) seeks to give the narratee (enunciate) an idea of a state of being and/or of an action.2) The subject of being for this state/action is the narrator, the narratee or a third person3) The responsible subject of doing for this state/action is the narrator, the narratee, the third person A or a fourth person B.A narrative, in the strict sense of this word, is a storytelling discourse, where neither the narrator nor the narratee is performing as subject of being and/or as subject of doing. Furthermore is the action closed, the narrator informs about events, which have taken place. The gospel of Mark can be viewed as a narrative in this sense, since neither the narrator Mark, nor his implied reader, is performing at the stage of its enunciate. The gospel narrative informs about many states and Actions, but the main theme is the realization of the kingdom of God, an action for which God ultimately is the responsible subject of doing (the fourth person B). Now the question is: “Whom is the subject of being favoured by this action?” In the first place the answer must be the third person A, the baptized or the chosen, i.e. persons performing in the enunciate of the narrative. But if the gospel is good news, then the narratee must see himself designated as a favoured subject of being, and another question arises: “How does the narration connect the narrative world with the reality of the reader?! It seems that such a connection can have a bearing upon time, place and/or person, and in the case of the gospel narrative it is upon time. The main action, the realization of the kingdom of God, is not finished in the story world, but will reach its end in the world of the reader (cf. the parable of the wicked husbandmen). By the establishment of this metonymical intercourse, the narration is symbolizing or semiotizing the reader, who receives his Christian identity and being from the narrative.